background image

We are going to consider (generalized) limits of arbitrary functions acting from

µ

to

ν

. (The

functions in consideration are not required to be continuous.)

Remark 12.

Most typically

G

is the group of translations of some topological vector space.

Generalized limit is defined by the following formula:

Definition 13.

xlim

f

=

def

{

ν

f

r

|

r

G

}

for any funcoid

f

.

Remark 14.

Generalized limit technically is a set of funcoids (see [2]).

We will assume that the function

f

is defined on

h

µ

i{

x

}

.

Definition 15.

xlim

x

f

=

def

xlim

f

|

h

µ

i{

x

}

.

Obvious 16.

xlim

x

f

=

{

ν

f

|

h

µ

i{

x

}

r

|

r

G

}

.

Remark 17.

xlim

x

f

is the same for funcoids

µ

and Compl

µ

.

Lemma 18.

(

A ×

FCD

B

)

f

=

h

f

1

iA ×

FCD

B

for every

f

FCD

,

A

,

B ∈

F

.

Proof.

For every filter object

X

h

(

A ×

FCD

B

)

f

iX

=

h

(

A ×

FCD

B

)

ih

f

iX

=

B

if

h

f

iX ∩ A

;

if

h

f

iX ∩ A

=

;

=

(

B

if

X ∩ h

f

1

iA

;

if

X ∩ h

f

1

iA

=

;

=

hh

f

1

iA ×

FCD

B iX

.

The function

τ

will define an injection from the set of points of the space

ν

(“numbers”, “points”,

or “vectors”) to the set of all (generalized) limits (i.e. values which xlim

x

f

may take).

Definition 19.

τ

(

y

) =

def

{h

µ

i{

x

} ×

FCD

h

ν

i{

y

} |

x

D

}

.

Proposition 20.

τ

(

y

) =

def

{

(

h

µ

i{

x

} ×

FCD

h

ν

i{

y

}

)

r

|

r

G

}

for every

x

D

.

Proof.

(

h

µ

i{

x

} ×

FCD

h

ν

i

y

)

r

=

h

r

1

ih

µ

i{

x

} ×

FCD

h

ν

i

y

=

h

µ

ih

r

1

i{

x

} ×

FCD

h

ν

i

y

=

h

µ

i{

r

1

x

} ×

FCD

h

ν

i

y

∈ {h

µ

i{

x

} ×

FCD

h

ν

i{

y

} |

x

D

}

where

x

D

.

Reversely

h

µ

i{

x

} ×

FCD

h

ν

i{

y

}

= (

h

µ

i{

x

} ×

FCD

h

ν

i{

y

}

)

e

where

e

is the identify element of

G

.

Theorem 21.

If

f

|

h

µ

i{

x

}

C

(

µ

;

ν

)

and

h

µ

i{

x

} ⊇ {

x

}

then

xlim

x

f

=

τ

(

fx

)

.

Proof.

f

|

h

µ

i{

x

}

µ

ν

f

|

h

µ

i{

x

}

ν

f

; thus

h

f

ih

µ

i{

x

} ⊆ h

ν

ih

f

i{

x

}

; consequently we have

ν

⊇ h

ν

ih

f

i{

x

} ×

FCD

h

ν

ih

f

i{

x

} ⊇ h

f

ih

µ

i{

x

} ×

FCD

h

ν

ih

f

i{

x

}

.

ν

f

|

h

µ

i{

x

}

(

h

f

ih

µ

i{

x

} ×

FCD

h

ν

ih

f

i{

x

}

)

f

|

h

µ

i{

x

}

=

h

(

f

|

h

µ

i{

x

}

)

1

ih

f

ih

µ

i{

x

} ×

FCD

h

ν

ih

f

i{

x

} ⊇

dom

f

|

h

µ

i{

x

}

×

FCD

h

ν

ih

f

i{

x

}

=

h

µ

i{

x

} ×

FCD

h

ν

ih

f

i{

x

}

.

Generalized limit

3